2013
DOI: 10.1007/s15010-013-0538-4
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of intracranial hypertension control in the management of Cryptococcus neoformans meningitis related to AIDS

Abstract: The results of this study confirm an association between HICP and mortality in patients with CMRA and indicate that the control of ICP during the first 5 days of hospitalization is more important than managing HICP only at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Several studies have reported that serial LPs to lower ICP during treatment of cryptococcal meningitis may improve outcomes [16], [17]. Although Malawian national guidelines suggest performing daily LPs during early therapy [9], there is neither adequate staffing nor the equipment for this to be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that serial LPs to lower ICP during treatment of cryptococcal meningitis may improve outcomes [16], [17]. Although Malawian national guidelines suggest performing daily LPs during early therapy [9], there is neither adequate staffing nor the equipment for this to be possible.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 A recent retrospective study suggests elevated ICP in patients with cryptococcal meningitis is associated with higher mortality and aggressive management of ICP during the initial 5 days was more important than initial antifungal management alone for survival. 12 Aspergillus Historically, disease from A fumigatus was limited to individuals with repetitive exposure to pathogens, producing a mild condition known as farmer's lung. Aspergillus subsp were also known to produce lung aspergillomas, characterized as an overgrowth of fungus in preexisting cavitary lung lesions.…”
mentioning
confidence: 99%
“…39 In another study, the incidence reported was higher among patients with severe bacterial meningitis (GCS score ≤ 8), wherein 93% of patients admitted to the neurointensive care unit developed intracranial hypertension. 21 Intracranial hypertension is not only limited to bacterial and viral infections, but also to parasitic and fungal pathogens, 4,8,29,49 e.g., Cryptococcus is particularly notorious for causing intractable ICP requiring CSF drainage. 8,23 Head CT is recommended in adults with suspected meningitis who present with focal neurological deficit or a decreased level of consciousness.…”
Section: Clinical Relevancementioning
confidence: 99%